Coleman Barks' Versions of Rumi in the USA. (July 2015) - Azadibougar, Omid; Patton, Simon
<x xml:space="preserve">Abstract</x> This paper examines Coleman Barks' English versions of Rumi to ask how he has rendered the original text and to explain the commercial success of his work in the American market. After describing the reception of Barks' versions and reflecting on the critiques of his work, we examine a translated poem from the Masnavi of Rumi as a sample case. This translation is marked by a transformation of poetic structure and substantial omissions from the source text. These features expose two conceptual tensions that interfere with Barks' work: the erotic content of a spiritual poem and the poem's elitist point of view. In this light we go on to discuss the translatability of literature and culture, challenges to world literature in translation, and the popularity of this version of Rumi in the USA.